Availability of Software-Based Correction of Mandibular Plane for the Vertical Measurement of the Mandible in Cone Beam Computed Tomography. (22nd October 2015) - Han, Sang-Sun; Lee, Kwang-Min; Kim, Kee-Deog
Abstract : Objectives . To investigate the availability of correction of mandibular plane using software for vertical measurements in cone beam computed tomography (CBCT) according to the sites of the mandible. Methods . CBCT scans of six dry mandibles were performed at 0-, 5-, 10-, 15-, and 20-degree angles relative to CBCT scanning table. Using the imaging software, mandibular planes of the different angles were corrected to that of 0-degree angle on the CBCT images. Before and after correction of the mandibular planes, the distance from the mandibular canal to the alveolar crest was measured at M1, M2, and M3 areas of the mandible and vertical measurements were statistically compared with those of 0-angle location using the paired t -test. Results . Prior to correction, the vertical measurements increased as the angle increased. The greatest differences of measurements were observed in M3 areas P < 0.05 . After correction, a strong correlation was found in measurements between the 0-degree angle and the other angles in all sites of the mandible P > 0.05 . Conclusions . The vertical measurements of CBCT were significantly influenced by mandibular positioning. When CBCT scans are performed at angles other than 0-degree angle, software-based correction of the mandibular plane can be a reliable tool for the accurate vertical measurements in CBCT.